Accumulation of radiation defects and modification of micromechanical properties under MgO crystal irradiation with swift 132Xe ions - Baubekova, G.; Akilbekov, A.; Feldbach, E.; Grants, Rolands; Manika, Ilze P.; Popov, Anatoli I.; Schwartz, K.; Vasil'Chenko, Evgeni A.; Zdorovets, Maxim V.; Lushchik, Aleksandr Ch (Elsevier B.V., 2020)
Accumulation of F-type defects under irradiation of MgO crystals by 0.23-GeV 132Xe ions with fluence varying by three orders of magnitude has been investigated via the spectra of optical absorption and low-temperature cathodoluminescence. The number of single centers continuously increases with fluence without any marks of saturation. At the highest fluence, a mean volume concentration of 3.1 × 1019 and 3.35 × 1019 cm−3 is reached for F and F+ centers, respectively. The F+ emission strongly dominates in the cathodoluminescence of irradiated MgO and its enhancement with fluence is detected. However, the creation efficiency of the F2 aggregate centers is very low and fluence dependence has a complicated shape. Radiation-induced changes of micro-mechanical properties of the same samples have been analysed; the depth profiles of hardening correlate with the ion energy loss. A joint contribution of ionization and impact mechanisms in the formation of structural defects under MgO irradiation with Xe ions is considered.
This work has been carried out within the framework of the EUROfusion Consortium and has received funding from the Euratom research and training programme 2014-2018 and 2019-2020 under grant agreement No. 633053. The views and opinions expressed herein do not necessarily reflect those of the European Commission. A.A. also acknowledges support via the project GF AP05134257 of Ministry of Education and Science of the Republic of Kazakhstan .
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics; Depth profile of hardening; Fluence dependence; Magnesium oxide; Optical absorption; Radiation defects; Swift heavy ions